Studi Kelayakan dalam Aspek Finansial pada Pengembangan Perumahan Ababil Land Babat Lamongan - Arif, Samsul; Syafrudianto, Ahmad Faisal; Agustapraja, Hammam Rofiqi (Jurnal Talenta Sipil, 2025)
Housing is one of the most popular investment objects in Indonesia. According to the Residential Property Price Survey, housing sales were unstable in 2024. Given this condition, a feasibility study is required for housing projects under development in 2024, particularly for subsidized housing types with relatively low prices, which may result in narrow profit margins. This study conducted a feasibility analysis of the Ababil Land Babat Lamongan housing project, specifically for the 30/60 type unit. This research aims to gather information on the profit margin achieved by the company and the overall investment feasibility of the project, providing valuable considerations for companies or developers in their decision-making processes. The method used in this study is a financial aspect approach, including Net Present Value (NPV), Internal Rate of Return (IRR), and Benefit-Cost Ratio (BCR). The results show that the project yields NPV = IDR 115,222,182.95 > 0, IRR = 7.65% > MARR = 6%, and BCR = 1.031 > 1. Therefore, it can be concluded that the Ababil Land Babat Lamongan housing investment project is financially feasible.